Apa Yang Memotivasi Seseorang Mengakses Aplikasi Mobile Laporkitong? Perspektif Teori Uses And Gratification (U&G) Dengan PLS-SEM - Azizah, Putri W; Inan, Dedi I; Sanglise, Marlinda (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Government Agencies BAPPEDA In Province Of Western New Guinea Utilizes A Technology By Making A Mobile Application Laporkitong Which Useful To Inform Incompatibility Of Using Soil. The Youth Laporkitong Application And Lack Of Knowledge Regarding This Application Made A Problem In Use. So That, It Is Necessary To Held An Analysis Why Individual Wants To Access Laporkitong Application By Using Uses And Gratification (U&G) Theory In Order To Maximize Its Function. In This Study, It Is Found A Consented Hypothesis Namely H5, H7, H8, H9. While A Rejected Hypothesis H1, H2, H3, H4, H6, H10. From This Study It Can Be Concluded That Motivating People To Intent Of Using Laporkitong Application Are Exposure, Social Sharing, And Affection. Then, Towards Intention Of Continuing By Using Application Is Social Sharing Variable. Also, Things Which Need To Repair Is A Prove That Not Influent To Intention Of Using Are Information Seeking, Entertainment And Intention Of Continuing Consume Are Information Seeking, Entertainment, Exposure, And Affection.